Gender relations, sexual behaviour, and risk of contracting sexually transmitted infections among women in union in Uganda - Nankinga, Olivia (BMC Public Health, 2016)
BACKGROUND: Sexually transmitted infections (STIs) are a major reproductive and public health concern, especially in the era of HIV/AIDS. This study examined the relationship between sexual empowerment and STI status of women in union (married or cohabiting) in Uganda, controlling for sexual behaviour, partner factors, and women’s background characteristics. METHODS: The study, based on data from the 2011 Uganda Demographic and Health Survey (UDHS), analysed 1307 weighted cases of women age 15–49 in union and selected for the domestic violence module. Chi-squared tests and multivariate logistic regressions were used to examine the predicators of STI status. The main explanatory variables included sexual empowerment, involvement in decision making on own health, experience of any sexual violence, condom use during last sex with most recent partner, number of lifetime partners and partner control behaviours. Sexual empowerment was measured with three indicators: a woman’s reported ability to refuse sex, ability to ask her partner to use a condom, and opinion regarding whether a woman is justified to refuse sex with her husband if he is unfaithful. RESULTS: Results show that 28 % of women in union reported STIs in the last 12 months. Sexual violence and number of lifetime partners were the strongest predictors of reporting STIs. Women’s sexual empowerment was a significant predictor of their STI status, but, surprisingly, the odds of reporting STIs were greater among women who were sexually empowered. Reporting of STIs was negatively associated with a woman’s participation in decision-making with respect to her own health, and was positively associated with experience of sexual violence, partner’s controlling behaviour, and having more than one life partner. CONCLUSIONS: Our findings suggest that, with respect to STIs, sexual empowerment as measured in the study does not protect women who have sexually violent and controlling partners. Interventions promoting sexual health must effectively address negative masculine attitudes and roles that perpetuate unhealthy sexual behaviours and gender relations within marriage. It is also important to promote marital fidelity and better communication within union and to encourage women to take charge of their health jointly with their partners. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-016-3103-0) contains supplementary material, which is available to authorized users.